Human T-lymphotropic virus infection and population characteristics of blood donors in Hainan - HUANG Yiqing; HAN Hui; ZHANG Jiongjiong; ZHANG Yongli (Zhongguo shuxue zazhi)
[Objective] To investigate the prevalence of human T-lymphotropic virus (HTLV) infection among voluntary blood donors and provide reference for the development of blood safety screening strategy in Hainan Province. [Methods] Enzyme linked immunosorbent assay (ELISA) was used to screen for HTLV, and the reactive samples were confirmed by Western blot (WB). [Results] A total of 326 269 blood samples from 2016 to 2023 in Hainan were screened, among which 117 samples showed reactive results for initial screening, with a reactive rate of 0.036% (117/326 269), and 9 were confirmed positive by WB, with a positive rate of 0.002 7%(9/326 269). The prevalence of HTLV antibody varied among different demographic groups, with a significantly higher rate among males compared to females (P<0.05). [Conclusion] There are HTLV antibody positive blood donors in the voluntary blood donors in Hainan. Although it is a low prevalence area for HTLV, it is necessary to continue to expand the blood screening and conduct epidemiological investigations on positive blood donors for blood safety.